High mobility group nucleosomal binding 2 reduces integrin α5/β1‐mediated adhesion of Klebsiella pneumoniae on human pulmonary epithelial cells via nuclear factor I. (29th October 2020) - Geng, Fan; Liu, Zhihao; Chen, Xingmin; Chen, Huan; Liu, Yanzhuo; Yang, Jing; Zheng, Min; Yang, Lu; Teng, Yan
Abstract: It has been reported that high mobility group nucleosomal binding domain 2 (HMGN2) is a nucleus‐related protein that regulates gene transcription and plays a critical role in bacterial clearance. An elevated level of HMGN2 reduced integrin α5/β1 expression of human pulmonary epithelial A549 cells was demonstrated during Klebsiella pneumoniae infection, thus weakening bacterial adhesion and invasion. However, the mechanism by which HMGN2 regulates integrin expression remains unclear. This study found that a transcription factor‐nuclear factor I (NFI), which serves as the potential target of HMGN2 regulated integrin expression. The results showed that HMGN2 was able to promote NFIA and NFIB expression by increasing H3K27 acetylation of NFIA/B promoter regions. The integrin α5/β1 expression was significantly enhanced by knockdown of NFIA/B via a siRNA approach. Meanwhile, NFIA/B silence could also compromise the inhibition effect of HMGN2 on the integrin α5/β1 expression. Mechanistically, it was demonstrated that HMGN2 facilitated the recruitment of NFI on the promoter regions of integrin α5/β1 according to the chromatin immunoprecipitation assay. In addition, it was further demonstrated that the knockdown of NFIA/B induced more adhesion of Klebsiella pneumoniae on pulmonary epithelial A549 cells, which could be reversed by the application of an integrin inhibitor RGD. The results revealed a regulatory role of HMGN2 on the transcription level of integrin α5/β1, indicating a potential treatment strategy against Klebsiella pneumoniae ‐induced infectious lung diseases.